Accommodation Services and Students’ Achievement in Public Secondary Schools in Southwest Nigeria - Aladetan, Femi Idowu; Adegun, Olajire Adeola (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The study investigated the relationship between accommodation services and students’ achievement in the cognitive and affective domains of learning in public secondary schools in Southwest, Nigeria. The study was a descriptive survey. The sample of the study was 108 principals, 1,080 teachers and 2,160 students selected across 108 public secondary schools in Southwest Nigeria. They were selected using multistage sampling procedure. The research instruments used for data collection were two researcher-designed questionnaire and a proforma. The questionnaire were titled ‘Accommodation Services Questionnaire (ASQ)’ and ‘Students’ Affective Questionnaire (SAQ) while he proforma is tagged ‘Student Academic Performance Proforma (SAPP). The test-retest method was used to ascertain the reliability of the instruments and the reliability coefficients obtained for ASQ and SAQ were 0.84 and 0.78 respectively. The research questions were answered using descriptive statistics while the hypothesis was tested using PPMC at 0.05 level of significance. Finding showed that the state of accommodation services in public secondary schools in Southwest Nigeria was favourable (x = 2.54); the level of students’ achievement in cognitive domain was high (x = 3.39); the level of students’ achievement in affective domain was moderate (x = 2.74). The relationship between accommodation services and students’ achievement was statistically significant (r = .448, p<.05). It was concluded that accommodation services positively relate to students’ achievement. It was therefore recommended that quality accommodation services should be provided by the government and school managers to students by ensuring the hostels are spacious, well-lit and well ventilated.